(untitled) (Boletin Médico de Postgrado, 2020)
In order to determine the risk factors associated with pregnancy induced hypertension of patients attended at the Hospital Acosta Ortiz in San Fernando de Apure during the period January-May 2016, a retrospective descriptive study was performed in 25 pregnant hospitalized patients. The majority of pregnant women were of relatively young age and 80% of them lived with their partners. The educational level was low; most of them only went to primary school. 60% of patients were housewives and 72% lived in overcrowded areas. With regard to biological factors, hypertension predominated in the parents of the patients; the majority had between 29 to 36 weeks of gestation and a large proportion of them had complications in previous pregnancies. Most of them had a high consumption of carbohydrates and saturated fats. Regarding psychosocial habits, 60% drank alcohol and 88% consumed caffeine. 10% performed physical activity and 8% recreational activities. 91% of patients attended prenatal consults of which 27% did not comply with the treatment and 30% did not follow the recommendations given by health personnel.